Positional Accuracy Measurement: Prototype Geographic Information System for Banyumas Regency Tourism - Priyono, Putra Aditya; Qalban, Anas Azhimi; Salma, Azora Sania (Transactions on Informatics and Data Science, 2025)
Banyumas Regency has high tourism potential, both in terms of nature, culinary, and culture. This study aims to assess the accuracy of geographic positioning (longitude and latitude) in a web-based Geographic Information System (GIS) to ensure the accurate and reliable presentation of tourist destination location data. Accurate spatial data is essential for planning, navigation, promotion, and improving visitor experiences through enhanced digital mapping and integrated tourism development strategies. The method used is prototyping, which allows the initial system development to be tested and refined based on the results of accuracy measurements. The system was developed using the Google Maps API and the PHP programming language and integrated with a GPS device to obtain real-time coordinates. Testing was conducted by comparing the field coordinates with digital map data to identify positional deviations. Analysis was carried out spatially using the Positional Accuracy Tolerance approach to improve the accuracy of the maps visualized in the Tourism Geographic Information System. The results of the study indicate the need for recalibration at several location points to improve the system's precision. This GIS is expected to provide valid location information for tourists in planning their tourism trips.